Journal of ‘Computers & Education’ from Past to Present: Bibliomeric Analysis (1978-2025) - Bulut, Aydın (Journal of Computer and Education Research, 2025)
This study presents a comprehensive bibliometric analysis of Computers & Education, a leading academic journal in the field of educational technology, covering the period from 1978 to 2025. Drawing upon data from the Web of Science database, a total of 4,715 articles were examined using bibliometric techniques, including co-citation, co-authorship, keyword co-occurrence, and thematic evolution analysis. The findings reveal a significant increase in publication volume and citation rates, particularly after 2008, indicating a growing scholarly interest in digital education. Thematic clustering analyses identified three dominant research foci: student performance and achievement, technology-enhanced learning and motivation, and user acceptance and self-efficacy. Furthermore, collaboration networks show that Taiwan, China, the USA, and the UK are central hubs in the global educational technology research landscape. Thematic evolution analysis reveals a paradigm shift from early discussions on "computer and distance education" toward more recent emphases on "digital content," "virtual learning," and "student-centered design." This study contributes to the literature by mapping structural patterns and identifying key trends, prolific authors, institutions, and countries, offering a macro-level understanding of how Computers & Education has shaped the educational technology discourse over nearly five decades.